HUBUNGAN EXPLOSIVE POWER OTOT LENGAN DAN BAHU DENGAN HASIL PUKULAN FOREHAND SMASH BULUTANGKIS PADA SISWA EKSTRAKURIKULER SMAN 1 SIMGPANG KANAN - Joko Irwanto; Ramadi '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The background of the problem in this study is not maximized yet forehand smash results conducted badminton extracurricular student at SMAN 1 Simpang Kanan. This problem is evident from observations of researchers at practice and games, it is suspected because of the explosive power of arms and shoulders of the students. Therefore, the purpose of this study was to determine whether there is a corelation explosive power of arms and shoulders with a forehand smash extracurricular students of SMAN 1 Simpang Kanan. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. As the independent variable (X) is the explosive power of arms and shoulders, while the dependent variable (Y) is a forehand smash badminton. This research data obtained from the tests using two hand medicine ball put test, and tests forehand smash badminton. The sample in this study were students extracurricular badminton SMAN 1 Simpang Kanan numbering 14 people (total sampling). Based on the research results can be concluded as follows: corelation variable X with variable Y obtained count r = 0.581> r table = 0.553, then there is a corelation between variables X with variable Y. Thus it can be said Ha Ho accepted and rejected. Conclusion The hypothesis was accepted at significance level α = 0:05 in other words there is a significant corelation between the explosive power arm and shoulder muscles with the result forehand smash badminton badminton male student extracurricular SMAN 1 Simpang Kanan.Keywords : Explosive Power, Arm and Shoulders Muscles, Smash, Badminton